Complications of ovariohysterectomy procedures performed in 1880 dogs - Muraro, L.; White, R. S. (Tierärztliche Praxis Ausgabe K: Kleintiere / Heimtiere, 2014)
Objective: Canine ovariohysterectomy (OVH) is one of the most commonly performed surgical procedures in companion animal practice. The aim of the study was to determine the frequency and types of complications related to OVH. Material and methods: The clinical records of all street dogs admitted to the public dog shelters of the Veneto Region (Italy) between January 2010 and December 2011 were reviewed for dogs that had undergone OVH. Specific comparison was made between anaesthesia time, body weight of the patients and intra-and postoperative complications (occurring up to 4 weeks postoperatively). The data were statistically analyzed. Results: Complications were recorded in 141 of 1880 bitches corresponding to an overall complication rate of 7.5%. Mean ± standard deviation (SD) weight of the bitches was 25.7 ± 6.7 kg and mean ± SD anaesthesia time was 42.8 ± 8.6 minutes. Distinct types of complications included significant ovarian artery haemorrhage, haemorrhage from the surgical wound, wound healing complications, urinary incontinence, ovarian remnant syndrome. Twenty-one patients had intraoperative complications and 120 patients had postoperative complications. Analysis of the grouped data showed a significant association between body weight and the incidence of complications. There was also a significant association between anaesthesia time and the incidence of complications. The results of this study indicate that patient weight is related to the incidence of complications and the odds of a complication occurring increase by a factor of 1.03 for every one kilogram of increase in patient weight. The period of general anaesthesia also appears to be related to the incidence of complications and the odds of a complication occurring increase by approximately 2% for each additional minute in anaesthesia time. Conclusion: Increasing patient weight and duration of anaesthesia time were found to be risk factors for the incidence of complications of OVH in the bitch.
Keywords: Surgery; ovariohysterectomy; complications; side effects; spaying